Análisis sobre la constitucionalidad de la facultad de la DIAN para seleccionar destinatarios de la acción penal (2022)
The Colombian legal system establishes three tax behaviors classified as crimes in the Colombian criminal code, which are: tax fraud or evasion, Omission of assets or declaration of these for a lower value or inclusion of non-existent liabilities in the income statement and Omission of the withholding agent or collector